Factors associated with stunting incidence in toddlers in Cibungbulang sub-district, Bogor - Marbun, Rosmida M.; Efiyanna, Rina; Meilinasari; Rabbani, Fairuz Dhia (International Journal Of Community Medicine And Public Health, 2024)
Background: Stunting is a developmental disorder characterized by L/A or H/A index z-score ≤2 SD and contribute to various negative impacts until adulthood. The prevalence of stunting among toddlers in Bogor Regency reached 24.9 percent according to SSGI. This study aimed to determine relationships between family income, being breastfed and drinking other milks, eating habits, handwashing and oral hygiene habits with stunting incidence among toddlers in Cibungbulang sub-district. Methods: The study used cross-sectional design with 307 samples selected through systematic randomization. Almost all data, except stunting, were collected through interview with respondents, while stunting was identified through height measurement. Results: Most toddlers had family income under the minimum wage (81.4%), did not drink breast milk anymore (52,4%), consumed other milks (60.6%), ate independently (69.4%), washed their hands after using toilets (91.2%), and cleaned their mouths at least once a day (85%). A total of 35% toddlers were stunted. There were significant relationships between family income (p=0.001), drinking breast milk (p=0.000) and other milks (p=0.001), eating habits (p=0.001), handwashing (p=0.035) and oral hygiene habits (p=0.039) with stunting incidence in toddlers (p<0.05). Conclusions: Family income, consumption of breast milk and other milks, eating habits, and handwashing and oral hygiene habits were associated with stunting in toddlers.